(untitled) (Journal of Economic Research & Business Administration, 2016)
The system of the higher education develops now in the context of market transformations therefore becomes possible and necessary to apply to its functioning some economic categories, such as: market, goods, demand, offer, competition, competitiveness. Today in the conditions of the market relations competitiveness acts, as the main driving force of development. For any country it depends on its natural and human potential. Thus many states proved more than once, what even at poverty of the first it is possible to be in number of the front lines and to take leading places in development. Therefore, a key factor is human potential and, first of all, education, competence and creative opportunities of people in the conditions of their realization. Knowledge becomes the main source of competitive advantages in the XXI century. However competitiveness of system of the higher education is determined, first of all, by competitiveness of higher education institution, his graduates and success of their work in various fields of activity. Speaking about results of the international comparison of system of the Kazakhstan higher education takes not leading positions in such aspect so far.